IZIN POLIGAMI DAN PERLINDUNGAN TERHADAP PASANGAN DI PA. SITUBONDO - Ahmad Sholehuddin; Idrus Idrus (Prodi Hukum Keluarga Fakultas Agama Islam Universitas Nurul Jadid, 2020)
Marriage is one of the most important aspects of life in a perfect society and association. Marriage is not only a noble way to organize domestic life and get offspring, but also an introduction between one family and another.Islam provides a way for men who want polygamy (marrying more than one person), which has been explained in the Al-Quran surah An-Nisa', with conditions that have been determined, one of which can be fair. The purpose of fair is fair treatment in serving the wife, both in terms of clothing, place, turn and others.the implementation of polygamy in Indonesia, must go through the Religious Court, the decision in the polygamy case, the judge only provides material protection, however, from the psychological aspect the judge does not provide protection, because the defendant has stated his ability to be polygamous, because the defendant cannot provide offspring, and he answered verbally before the Panel of Judges.